2016
DOI: 10.1111/sode.12224
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control, peer preference, and loneliness in Chinese children: A three‐year longitudinal study

Abstract: The purpose of this study was to explore the longitudinal links among Chinese children's self-control, social experiences, and loneliness, largely from a developmental cascades perspective (which postulates mechanisms about how effects within a particular domain of functioning can impact across additional domains over time). Participants were N 5 1,066 primary school students in Shanghai, P. R. China, who were followed over three years from Grade 3 to Grade 5. Measures of children's behavioral self-control, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 76 publications
1
28
1
Order By: Relevance
“…The independent samples t test was used to explore the gender difference in children's loneliness ( t = 1.96; p = .050). Although our study found no significant differences of age and gender on children's loneliness, the previous studies demonstrated that children's age and gender were closely related to their loneliness (Mercer & Derosier, ; Liu et al, ). Therefore, these three variables (region, age, and gender) were controlled in the following analyses.…”
Section: Methodscontrasting
confidence: 96%
See 3 more Smart Citations
“…The independent samples t test was used to explore the gender difference in children's loneliness ( t = 1.96; p = .050). Although our study found no significant differences of age and gender on children's loneliness, the previous studies demonstrated that children's age and gender were closely related to their loneliness (Mercer & Derosier, ; Liu et al, ). Therefore, these three variables (region, age, and gender) were controlled in the following analyses.…”
Section: Methodscontrasting
confidence: 96%
“…The standardized score was regarded as the index of peer acceptance. The peer nomination task has been widely used in Chinese children (Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of long-term negative family environment on loneliness is not effectively moderated by self-control (Betts and Rotenberg, 2010). A research by Liu et al (2017) revealed that loneliness has strong stability and durability, and is difficult to alter through positive psychological traits such as self-control. In conclusion, adolescents who have experienced childhood maltreatment, even though they are no longer abused, can still suffer from problematic behavior and cognition, and this influence is difficult to moderate through self-control.…”
Section: Discussionmentioning
confidence: 99%